WHEN SARCOIDOSIS CHALLENGES PERFORMANCE: PULMONARY AND SPLENIC DISEASE IN A YOUNG ATHLETE - Jan Kamiński; Sebastian Rurka; Julia Dolinkiewicz; Agnieszka Szczerbińska (International Journal of Innovative Technologies in Social Science, 2025)
Sarcoidosis, also known as Besnier-Boeck-Schaumann disease, is a granulomatous disease of unknown etiology, with multisystemic manifestations that can affect performance and physical capacity in athletes. In most early-stage cases (stage I and II), the disease may resolve spontaneously without treatment. However, when sarcoidosis presents with atypical features such as splenomegaly, especially in physically active individuals or athletes, the prognosis may be more severe, potentially affecting exercise tolerance, recovery time, and return to training. A comprehensive diagnostic approach, combining clinical evaluation with radiological and histopathological confirmation, is essential. Splenomegaly has been associated with poorer outcomes in pulmonary sarcoidosis compared to favorable signs like erythema nodosum or arthritis. This article presents the case of a 22-year-old female patient, whose pulmonary sarcoidosis was complicated by splenomegaly. The case underlines the importance of early recognition in active individuals and timely intervention to improve prognosis and preserve physical performance. Methods: The authors reviewed literature from ScienceDirect, Cochrane Library, PubMed, Google Scholar, and UpToDate, focusing on sarcoidosis. The review emphasized the importance of combining clinical, radiological, and histopathological data for diagnosis, and noted that splenomegaly worsens prognosis in pulmonary sarcoidosis, while erythema nodosum and arthritis are linked to better outcomes. Conclusions: In physically active patients, especially athletes, atypical manifestations such as splenomegaly in pulmonary sarcoidosis may lead to significant performance decline and delay in returning to training. Early diagnosis and treatment are crucial not only for controlling disease progression but also for minimizing long-term impact on aerobic capacity, muscle strength, and recovery time. Clinicians should consider sarcoidosis in the differential diagnosis of unexplained fatigue, dyspnea, or decreased performance in young athletes.